Development Of E-Health In Austria, Bulgaria, Croatia, Estonia And Slovakia - Georgiev, Angel Atanasov; Shtereva-Tzouni, Doroteya (Archives of Business Research, 2020)
Electronic health services (e-Health) are now a fixed element of the health care system and cover a wide range of applications, such as the electronic health insurance card, the health record and an overview of medications, plus telemedicine. A prerequisite for this is the secure transmission of medical data for preventive medicine, diagnosis, treatment and the ongoing support of patients in the form of text, sound recordings and/or images. Uneven development of eHealth solutions within the EU27 remains a major obstacle in providing European citizens with a satisfying access to cross-border healthcare and the main challenge for the EU is harmonizing the systems. The slow shift of the paradigm centralizing the role of the patient will become more rapid making our assumptions about the savings thanks to the technology even more conservative than they are. Building on the trust that Europeans have in health institutions and the way they convey themselves is essential.